ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEREKONOMIAN, KONSUMSI DAN INVESTASI DI SUMATERA BARAT - Gulanda, Sonya; Amar, Syamsul; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2013)
This study aims to analyze and determine (1) the influence of consumption, investment, government spending, and net exports to the economy in West Sumatra, (2) the influence of the economy, disposable income of the previous period, the consumption of the previous period and the rate of consumption to consumption in West Sumatra (3) the influence of the economy, the investment rate, and the rate of investments in West Sumatra. Type of data is the documentary data, the data source is a secondary data as well as data in the form of time series from the first quarter of 2000 - the fourth quarter of 2012. This study uses a simultaneous equation model analysis tool with Two Stages Least Squared method (TSLS). Endogenous variables in the study was the economy, consumption and investment. While the disposable income variable is exogeneous previous period, the consumption of the previous period, real interest rates, exchange rates, government spending, and net exports. The research concludes that (1) Variable consumption, investment, government spending and net exports have a significant effect on the economy in West Sumatra. (2) Variable economy, disposable income of the previous period, and previous period consumption in West Sumatra affect consumption significantly. While the real interest rate variable does not significantly influence consumption in West Sumatra. (3) The economy, investment and interest rates have a significant effect on investment in West Sumatra. Whereas no significant effect on the rate of investment in West Sumatra. Based on these results the policies that can be suggested is the Local Government (LG) West Sumatra needs to provide incentives to productive sectors, addition, West Sumatra government needs to provide incentives to investors. Diversty export products needs to be improved as well as the local and export destinations of West Sumatra so that the increase in exports can be realized with either. Keywords: economy, consumption and investment, disposable income the previous period, the consumption of the previous period, real interest rates, exchange rates, government spending, and net exports.